Giant internal iliac artery aneurysm successfully treated with endovascular stent-graft placement - Hatzidakis, Adam (Interv Med Appl Sci, 2018)
An 88-year-old male patient of high surgical risk was presented with left sciatic pain symptoms and a palpable pulsatile left lower abdominal mass. He was operated 8 years ago for a large infrarenal aortic aneurysm. Computed tomography angiography (CTA) revealed a giant 161 mm left internal iliac aneurysm with multilocular appearance and left sacral bone erosion causing the symptoms. Endovascular repair was successfully performed using a monotubular iliac stent-graft. Follow-up CTA showed absence of contrast enhancement and a fully thrombosed sac. Patient recovered completely and was discharged 1 month after the procedure in a relatively good condition, nevertheless sciatic symptoms remained.